Τhe symbolic economy of cities – new shapes of work and networking: Τhe role of traditional and emerging clusters of creativity in the Αthenian public space - Koutsari, Maria; Demertzi, Aggeliki (The Greek Review of Social Research, 2020)
In this article we investigate the changes in the Athenian urban space that have taken place in the light of the crisis, changes in labour relations and the symbolic economy. In the first part a theoretical overview of international changes, the role of culture in development strategies and the symbolic economy is made. Urban policies and new shapes of work are also being analyzed. The case of the historic centre of Athens, as a host of creative activities and as a growing tourist destination, also comes to the forefront. The last part is devoted to the ongoing field research conducted to look into the traditional and emerging creativity clusters in the center of Athens, how they are built and located and their interaction with the Athenian Urban Factory.